2019
DOI: 10.1186/s13287-019-1331-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of culture media on large-scale expansion and characteristic of adipose tissue-derived mesenchymal stromal cells

Abstract: Background Adipose tissue-derived mesenchymal stromal cells (ASCs) have been shown to exhibit some promising properties of their use in regenerative medicine as advanced therapy medicinal products (ATMP). However, different sources of their origin, methods of isolation, and expansion procedures cause the laboratory and clinical results difficult to compare. Methods ASCs were isolated from lipoaspirates and cultured in three different medium formulations: αMEM and DMEM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 50 publications
5
49
0
1
Order By: Relevance
“…In another study, a higher immunosuppressive effect was observed for BM-MSCs expanded in HPL-supplemented media (Gottipamula et al, 2012). Other studies comparing cell expansion in HPL-or FBS-supplemented media have reported no difference in the immunosuppressive effects of BM-MSCs (Bieback et al, 2009), or in the secretion profiles of A-MSCs (Czapla et al, 2019). Chromosomal stability appeared to be the same if not better for cells grown in HPL (Shih and Burnouf, 2015;Astori et al, 2016).…”
Section: Cell Culture Supplementsmentioning
confidence: 87%
See 1 more Smart Citation
“…In another study, a higher immunosuppressive effect was observed for BM-MSCs expanded in HPL-supplemented media (Gottipamula et al, 2012). Other studies comparing cell expansion in HPL-or FBS-supplemented media have reported no difference in the immunosuppressive effects of BM-MSCs (Bieback et al, 2009), or in the secretion profiles of A-MSCs (Czapla et al, 2019). Chromosomal stability appeared to be the same if not better for cells grown in HPL (Shih and Burnouf, 2015;Astori et al, 2016).…”
Section: Cell Culture Supplementsmentioning
confidence: 87%
“…HPL provides strong growth-promoting activity to support the expansion of a variety of cells (Choi et al, 1980;Eastment and Sirbasku, 1980;Hara et al, 1980). In fact, there are now ample studies demonstrating that proliferation of MSCs from various tissue sources is higher when HPL is used (Schallmoser et al, 2007;Bieback et al, 2009;Gottipamula et al, 2012;Gottipamula et al, 2013;Gottipamula et al, 2016;Czapla et al, 2019;Kakudo et al, 2019) and generally studies utilizing HPL for in vitro expansion of MSCs have found it to be an acceptable alternative to FBS in terms of maintaining cellular features for clinical applications (Fekete et al, 2012;Becherucci et al, 2018). However, studies on the effects of HPL on the immunosuppressive capacity of MSCs have been contradictory.…”
Section: Cell Culture Supplementsmentioning
confidence: 99%
“…In a recent study, αMEM and DMEM as basal media supplemented with 10% of human platelet lysate (hPL) and DMEM supplemented with 20% fetal bovine serum (FBS) and bFGF were compared in culturing adipose tissue-derived mesenchymal stromal cells (ASCs). The results indicate thatαMEM supplemented with 10% hPL yield the highest proliferation rate and rate of clonal genic potential, while no differences in adipocyte, osteocyte, and chondroblast differentiation [20]. This study was done with ASCs.…”
Section: Comparison Of Cell Surface Marker Detectionmentioning
confidence: 87%
“…A variety of protocols are described for GMP MSC production, some of these using selected FBS, others using xeno-free components, HPL, or plasma. As MSCs are considered ATMPs, qualified protocols with standardised characteristics are needed so that MSCs can be developed in large-scale quality and at a relatively low-cost of production using xeno-free media for clinical-grade expansion [ 25 , 26 ]. In recent years, we have been establishing methods to isolate and expand MSCs for clinical use, and we have also demonstrated that iHPLs prepared in-house from a large pool of donor platelets, that undergo pathogen inactivation using psoralen, are safer and more efficient than FBS in isolating BM-MSCs when following GMP guidelines [ 8 , 27 ].…”
Section: Discussionmentioning
confidence: 99%